Impact of Ocean Acidification and Warming on the bioenergetics of developing eggs of Atlantic herring Clupea harengus. Issue 1 (18th September 2018) - Leo, Elettra; Dahlke, Flemming T; Storch, Daniela; Pörtner, Hans-O; Mark, Felix C
Abstract : Ocean Acidification and Warming induce trade-offs in development and growth of Atlantic herring embryos by altering mitochondrial function and increasing the animal's energy demand. Abstract: Atlantic herring ( Clupea harengus ) is a benthic spawner, therefore its eggs are prone to encounter different water conditions during embryonic development, with bottom waters often depleted of oxygen and enriched in CO2 . Some Atlantic herring spawning grounds are predicted to be highly affected by ongoing Ocean Acidification and Warming with water temperature increasing by up to +3°C and CO2 levels reaching ca. 1000 μatm (RCP 8.5). Although many studies investigated the effects of high levels of CO2 on the embryonic development of Atlantic herring, little is known about the combination of temperature and ecologically relevant levels of CO2 . In this study, we investigated the effects of Ocean Acidification and Warming on embryonic metabolic and developmental performance such as mitochondrial function, respiration, hatching success (HS) and growth in Atlantic herring from the Oslo Fjord, one of the spawning grounds predicted to be greatly affected by climate change. Fertilized eggs were incubated under combinations of two P CO2 conditions (400 μatm and 1100 μatm) and three temperatures (6, 10 and 14°C), which correspond to current and end-of-the-century conditions. We analysed HS, oxygen consumption (MO2 ) and mitochondrial function of embryos as well as larval length at hatch. The capacity of the electron transport system (ETS) increased with temperature, reaching a plateau at 14°C, where the contribution of Complex I to the ETS declined in favour of Complex II. This relative shift was coupled with a dramatic increase in MO2 at 14°C. HS was high under ambient spawning conditions (6–10°C), but decreased at 14°C and hatched larvae at this temperature were smaller. Elevated P CO2 increased larval malformations, indicating sub-lethal effects. These results indicate that energetic limitations due to thermally affected mitochondria and higher energy demand for maintenance occur at the expense of embryonic development and growth.